ELEKTR ENERGIYASI TEJAMKORLIGI - Yo’lchiev M .; To’raqulov Dostonbek Rustamjon o‘g‘li; Raxmatullayev Shamsiddin Hakimboy o‘g‘li (Лучшие интеллектуальные исследования, 2024)
Abstract: Improving the efficiency of electricity in today's industries and enterprises and preventing existing wastages is a problem for all of us. Achieving good results is also an increase in efficiency. Concepts of energy efficiency are reflected in all fields, and this article deals with the problem of efficient use of electricity in some fields.